DEVELOPMENT AND CHARACTERIZATION OF BIOFILMS FROM MIXTURES OF CORN - POTATO STARCH, SORBITOL AND OREGANO ESSENTIAL OIL (Origanum vulgare) - León Moncada, Alexandra (2022)
In the present work, biofilms were elaborated by means of the casting method using a 2x2x3 multilevel factorial design with a replica, being the factors: sorbitol concentration (60% and 80%), process temperature (85°C and 95°C) and proportions of potato starch (P) and corn starch (M): 0%M:100%P, 25%M:75%P and 50%M:50%P, for the determination of the best formulation based on their mechanical properties: tensile strength (RT, MPa) and elongation (E, %). The results were accepted with a 95% confidence level (p < 0.05) and by comparison of LSD means. The selected treatment was obtained using sorbitol at 60%, process temperature at 95°C and mixing ratio at 50%P:50%M, obtaining 6,23 N/mm2 of RT and 14,67% of elongation. This formulation was used as a polymeric base for the second stage, where 0, 1 and 2,5% of oregano essential oil (AEO) was added using an individual categorical factor design, in which the influence of AEO on antimicrobial activity was determined. The biofilm with 1% AEO was selected, with a 95% confidence level (p < 0,05), which showed an N/mm2 value of 4,03 MPa, 30,21% E, and antimicrobial activity against Staphylococcus aureus, followed by Bacillus cereus. All results were evaluated by analysis of variance (ANOVA) and accepted at a 95% confidence level (p < 0,05).